2014
DOI: 10.1021/jp4103542
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation and Site Dependent Charge Transfer Dynamics at PTCDA/TiO2(110) Interface Revealed by Resonant Photoemission Spectroscopy

Abstract: Charge transfer dynamics across the interface of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) organic molecules and the reduced rutile TiO 2 (110) 1 × 1 surface has been investigated using core-hole clock implementation of resonant photoemission spectroscopy (RPES). It is found that ultrafast charge transfer from PTCDA molecules to TiO 2 substrate takes place on the time scale of 8−20 fs due to their strong electronic coupling. Moreover, the charge transfer time scale at the PTCDA/TiO 2 (110) interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…One can easily observe from the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 HOMO peak (fig 1) shows that HOMO-LUMO gap increases with exposure. This indicates that the rubrene films become more insulating with ambient exposure 24,25 . The peaks labeled α and γ are assigned to transitions from carbon atoms at the tetracene backbone whereas the peak labeled β is mostly associated to the excitations within the four phenyl side groups of rubrene 26 .…”
Section: ■ Computational Methodsmentioning
confidence: 98%
“…One can easily observe from the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 10 HOMO peak (fig 1) shows that HOMO-LUMO gap increases with exposure. This indicates that the rubrene films become more insulating with ambient exposure 24,25 . The peaks labeled α and γ are assigned to transitions from carbon atoms at the tetracene backbone whereas the peak labeled β is mostly associated to the excitations within the four phenyl side groups of rubrene 26 .…”
Section: ■ Computational Methodsmentioning
confidence: 98%
“…The local molecular orientation resembles that observed for perylenetetracarboxylic-dianhydride, PTCDA, 24 which was reported to favor a fast (dynamical) charge transfer from the molecule to the substrate. 25 The oxidation state of the molecule in the overlayer can be monitored by comparing the occupied and unoccupied molecular orbitals, MOs, as measured by X-ray photoemission (XPS) and near-edge X-ray absorption spectroscopy (NEX-AFS), respectively. The charge distribution in the surface and near surface layers of TiO 2 can be probed by measuring the characteristic DS in the gap of titania that occurs upon injection of electrons (independently of the mechanism 8,17,26 ).…”
mentioning
confidence: 99%
“…Komolov et al [27] and Cao et al [2930] investigated very high coverage densities, i.e., multilayer assemblies (up to a few nanometres thick) of molecules on the (110) face of rutile titania using spectroscopic techniques. For a few nanometre thick overlayers, the formation of an interfacial potential barrier due to band bending in the substrate, the molecular polarization in the organic film, and an increase in the work function have been reported [27].…”
Section: Reviewmentioning
confidence: 99%
“…For a few nanometre thick overlayers, the formation of an interfacial potential barrier due to band bending in the substrate, the molecular polarization in the organic film, and an increase in the work function have been reported [27]. More detailed analyses of the electronic structure, molecular orientations, energy level alignment and charge transfer dynamics have been provided by Cao et al [2930]. The authors showed that strong coupling between the PTCDA molecules and the TiO 2 substrate results in charge transfer time scales of the order of 8–20 fs [30].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation